Adaptabilidade e estabilidade de genótipos de bananeira em diferentes condições ambientais - Alves, Juliana da Silva (2009)
The objective of this work was to evaluate the behavior of genotypes of banana, in different locations and identify superior genotypes, aiming to recommend them to more than one ecosystem. The evaluated genotypes were: Japira, Pacovan Ken, Pacovan, Prata Anã, Calispo, Ambrosia e Grande Naine. Data from five locations: Campos-RJ, Guanambi-BA, Una-BA, Petrolina-PE and Cruz das Almas-BA, for two production cycles, were considered. The statistical method was used blocks randomized, with 7 treatments and 3 repetitions, in a spacing of 3,00 m x 2,00 m. The Grande Naine cultivar presented promising agronomic characteristics in most locations evaluated for both production cycles. The cultivars Grande Naine and hybrids Ambrosia and Calipso ranked among the first classifications, with good adaptability and stability.